The Creation of Man in Tafsir Al-Jawahir by Thanthawi Jawhar - Alya Muhibah; Heru Apriliaji; Mochammad Luthfie; Muhammad Haikal Pasha; M. Sugino Ramdhan; M. Ja’far Shodiq; Say Futriana; Widya Rosi Juliyanti (al-Afkar, Journal For Islamic Studies, 2025)
This research examines the concept of human creation according to Tafsir Al-Jawahir by Tantawi Jawhari, a commentary that combines interpretation of the Al-Qur'an with a scientific approach. This tafsir highlights how the Qur'an explains the creation of humans through several stages, starting from the earth to becoming perfect creatures. The process of human creation includes the phases of germfah (semen), alaqah (a clot of blood), mudghah (a clot of flesh), bone formation, and the impregnation of the spirit that brings human life. Tantawi uses the "tahlili" exegetical method, which emphasizes in-depth and comprehensive explanations of the meaning of Al-Qur'an verses, and links them to modern science such as biology and embryology. This research also shows that Tantawi includes elements of science in his interpretations, such as images of plants, animals and natural phenomena, to strengthen the reader's understanding of the process of human creation.Through this approach, Tantawi wants to show that there is no conflict between the Koran and science, in fact the Koran precedes science in explaining many natural phenomena. This study employed a qualitative method with a literature review approach, with the primary data sources being the Tafsir Al-Jawahir and other secondary sources. The results revealed that Tantawi successfully connected the concept of human creation in the Qur'an with modern scientific theories, ultimately demonstrating God's greatness and power in the creation of living things.